Domestic demand and exports: Evidence from Turkish firms - Selçuk Gül (Central Bank Review (CBR), 2021)
This study examines the relationship between real domestic sales and real exports for Turkish manufacturing firms. Dynamic panel data estimations based on firm-level data for the period 2004-2014 suggest that the two variables are substitutes. Other factors held constant, we estimate that a 10 percent decline in real domestic sales is associated with around 2.7 percent increase in real exports, on average. However, this relationship varies among manufacturing sub-sectors which are defined according to 2-digit NACE classification. Results indicate that substitutability between domestic and foreign sales is stronger for export-oriented, low-leveraged and younger firms and firms that operate in sectors whose exports are less import-dependent. Besides, the degree of substitution between the two variables significantly rises when domestic demand conditions are weak. This shows that exporter firms in the Turkish manufacturing industry can shift from domestic to international markets as a response to domestic demand shocks.
Keywords: C23; D22; F14; 330; Domestic sales; Domestic demand; Exports; Dynamic panel data